Batasan Kepemilikan Satuan Rumah Susun Oleh Warga Negara Asing - Egarini, Putu Wahyu Ning; Bagiastra, I Nyoman (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 9 No 01 (2024), 2024)
This research to analyse the regulation of ownership of apartment units by foreigners after the issuance of Law No. 6 of 2023 on the Stipulation of Government Regulation in Lieu of Law No. 2 of 2022 on Job Creation into Law, this research analyses the legal certainty of ownership of apartment units by foreigners. This research uses normative legal research based on the conflict of norms between the Basic Agararia Law and Law No. 6 of 2023 by using a statutory approach (statue approach) by examining related laws. The results of this research show that the construction of flats can be built on land with the right to build or the right to use on the right to build. The application of the principle of horizontal separation results in ownership of flats by foreigners only limited to the right to use the flat unit, foreigners can own a flat unit but not accompanied by land ownership. The opportunity given to foreigners to own flats is not in accordance with the principle of equitable land distribution. Horizontal separation is shown on the Certificate of Ownership of Flat Unit (SHMRS) with legal consequences if in the future problems arise with the flat building such as natural disasters, building collapse, fire then the ownership period of the Certificate of Ownership of Flat Unit (SHMRS) ends. Ownership of flats has restrictions stipulated in Article 71 of Government Regulation No. 18 of 2021 regarding the minimum price, area, number of plots of land or units of flats.